Hospital accreditation and its impacts on good practices in health services - Rodrigues Terra, José Daniel; Tobal Berssaneti, Fernando (O Mundo da Saúde, 2017)
The Brazilian health system has undergone profound transformations. Hospital institutions have been adopting quality management programs with the objective of continuously improving their processes, products and services, using accreditation as methodology for the external evaluation of quality in health services. This article analyzes the impacts generated by this accreditation in the creation of good quality practices in health services. It uses a qualitative approach, with multiple case studies, conducted in five different hospitals, from November 2015 to February 2016, through interviews and with the aid of a semi-structured questionnaire. The results show that upper management support is relevant to the processes of continuous improvement, and to increase productivity in services. Also, patient safety levels are related to improvements in the quality of care. It is concluded that good quality practices in health services in hospitals, when associated with accreditation, increase productivity, increase patient satisfaction and add value to the institution.